A study on awareness of HIV among first year MBBS students in a private Medical College, Kerala, India - B. C., Satheesh; S. A., Thilak; A. K., Sarada; K. V., Madusoodanan; P. P., Venugopalan (International Journal Of Community Medicine And Public Health, 2017)
Background: India has the third largest HIV epidemic in the world with 2.1 million Indians accounting for about four out of 10 people infected with the deadly virus. The lack of awareness and misconceptions about HIV/AIDS is responsible for rapid spread in our country. Many studies reported that early educational intervention has the potential to bridge the gap both in knowledge and the negative attitudes directed towards those with HIV infection. This study was conducted to assess awareness regarding HIV/AIDS in newly admitted medical students and to assess awareness regarding HIV/AIDS among first year medical students of a private medical college in Kerala, India. Methods: A cross sectional study was conducted on first year MBBS students of a private medical college, Kerala. A total of 135 students were interviewed using pre-validated, semi structured questionnaire. Descriptive statistics were used to analyze the data. Results: All the students (100%) were aware about HIV/AIDS disease, its causative agent and diagnostics test. Majority of the students were aware about the modes of transmission and preventive approaches. A few of the respondents believed wrongly that the virus can be transmitted through mosquito bite, by hugging and kissing, through urine as well as sharing of same toilet seats and clothes with an infected person. Conclusions: Our study demonstrates an overall satisfactory level of awareness on routes of transmission and prevention of HIV/AIDS. A continuous such surveys at regular intervals would further help to assess the level of awareness and attitude towards HIV/AIDS for designing future educative programmes.